Магия башкирского тамбура - Камалиева Айгуль Салаватовна (Китап, 2021)
Экземпляры: ОБСЛ (20221219) / Инвентарный номер: 1123308 / Цена: / Сис.шифр: 85.12 / Авт.знак: К 18 / ГРНТИ: 18 / ББК: 85.126.9^VLBC/M